From seeing to saving: How rhinoceros-based tourism in north-west Namibia strengthens local stewardship to help combat illegal hunting - Muntifering, Jeff R.; Malherbe, Andrew; Dax, Lorna; Beytell, Piet (Frontiers in Sustainable Tourism, 2023)
The opportunity to encounter wildlife, especially endangered species, has long been a major tourism draw for countries around the world with demand continuing to grow. Yet direct evidence testing the underlaying assumptions of tourism as a wildlife conservation strategy has been more limited particularly where tourism benefits are assumed to “trickle down” to rural communities that foster local stewardship. A long-term case study from north-west Namibia's communal lands presents and evaluates a theory of change for a community-level black rhinoceros conservation tourism model that explicitly incorporates local values and institutions in design expected to deliver results that enhance local-level stewardship and improving conservation outcomes for the population. Between 2012 and 2018, the numbers of tourists participating in and revenue generated from local ranger-based rhinoceros viewing encounters directly to local community institutions increased dramatically by over 200% with over USD 1,000,000 generated during the 6 year period. Subsequent community re-investments in rhinoceros protection was evidenced by a 340% increase in the employment of local “Rhino Rangers” during the same period. Further, a strong positive relationship between community institutions that directly provide support to and benefit financially from tourism with the level of their reinvestment in rhinoceros conservation suggest that communities that benefited more from rhinoceros-based tourism demonstrated higher levels of stewardship. A strong negative relationship observed between rates of illegal hunting of the rhinoceros population and the level of local rhinoceros protection efforts suggest that the increase in local stewardship likely contributed to the reduction in illegal hunting. The Namibia Conservancy-led rhino conservation tourism case offers evidence and lessons that illustrate how carefully curated wildlife tourism that is designed specifically with community engagement and empowerment in mind may serve as a strong basis for enhanced local stewardship that helps improve wildlife and local human communities.